Elucidating the narrative structure of arguments for moral contractarianism - de Araujo, Marcelo (Filosofia Morale/Moral Philosophy, 2023)
If the nature of an agreement is such that it is binding upon the agreeing parties, then before an agreement is made the parties to the agreement have to share the common understanding that, by agreeing, they have an obligation to act as agreed. But where does that shared understanding come from? Does the shared understanding simply dawn on them the moment they agree to do something, or do they already share that understanding before they agree? The assumption that the very idea of an agreement cannot be established by means of an agreement and that, for this reason, social contract theories have to rely on at least some basic normative ideas for the establishment of less basic normative ideas has been a common line of criticism against moral contractarianism. It does not follow from this, though, that supporters of contractarianism cannot answer this objection. In this paper, I argue that contractarianism can, indeed, tackle this problem.